2014
DOI: 10.3109/13880209.2013.876654
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofl-arginine and creatine administration on spatial memory in rats subjected to a chronic variable stress model

Abstract: Overall, these results demonstrated that a single administration of creatine improves working memory efficiency, and, when co-administrated with l-arginine, improves reference memory retention, a phenomenon that is possibly associated with increased creatine/phosphocreatine levels and l-arginine-derived NO synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In healthy adults, tyrosine improved cognitive performance, especially in stressful conditions [ 48 , 49 ] and histidine shortened reaction time on a working memory task [ 50 ]. Glutamic acid improved learning and memory in rats [ 51 ] and arginine improved cognitive function in humans [ 52 ], showed antioxidant neuroprotective effects [ 53 , 54 ] and improved working memory [ 55 ] and spatial memory [ 53 , 55 ] in rats. BCAA supplementation has been studied in adult athletes and shown to improve cognitive function [ 56 , 57 , 58 , 59 ] due to modulation of neurotransmitter (serotonin and the catecholamines) synthesis and release [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…In healthy adults, tyrosine improved cognitive performance, especially in stressful conditions [ 48 , 49 ] and histidine shortened reaction time on a working memory task [ 50 ]. Glutamic acid improved learning and memory in rats [ 51 ] and arginine improved cognitive function in humans [ 52 ], showed antioxidant neuroprotective effects [ 53 , 54 ] and improved working memory [ 55 ] and spatial memory [ 53 , 55 ] in rats. BCAA supplementation has been studied in adult athletes and shown to improve cognitive function [ 56 , 57 , 58 , 59 ] due to modulation of neurotransmitter (serotonin and the catecholamines) synthesis and release [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that an even longer time period is required to enhance brain creatine levels. On the other hand, it is also possible that creatine supplementation might only work on brain performance when deficient in the first place, or when challenged with various stressors [8,10,11].…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies in healthy adults have found no cognitive benefit to creatine supplementation [7] and possibly, the cognitive effects of creatine supplementation may only be apparent during stress or when exogenous supply or endogenous synthesis is restricted. Indeed, studies in rats show improved efficiency with spatial working memory during chronic stress following a single creatine dose [8]. Whereas mice chronically supplemented with creatine elicited better performance on a variety of memory tasks and had improved mitochondrial energetics [9].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, arginine and pyridoxal 5'-phosphate biosynthesis pathways were specifically reduced in C-ADHD patients. Arginine, a precursor of nitric oxide, is related to better memory [35] and improved intestinal inflammation [36]. Pyridoxal 5'-phosphate is a dominant vitamin B6 active type, and serum vitamin B6 was decreased in ADHD patients [37].…”
Section: Discussionmentioning
confidence: 99%